Examining Age Diversity, Gender Diversity and Teaching Performance in Higher Education in the Kathmandu Valley - Gharti, Amit (Nepal Journal of Multidisciplinary Research, 2023)
Educational institutions worldwide strive for enhanced teaching quality and equitable practices, this brings understanding the potential influence of demographic factors on teaching effectiveness has become crucial. In this regard, the study focused on examining Age Diversity, Gender Diversity and Teaching Performance in Higher Education in the Kathmandu Valley. The study draws on comprehensive data collected from 421 faculty members utilizing a quantitative method. The study is confined solely to private management colleges and the primary tool utilized to gather data was a questionnaire. Frequency, Chi-square, and Pearson Correlation were used as a means to assess the objective. Findings show that private management colleges in the Kathmandu Valley have given greater importance to age with the intention of improving the performance of their teaching faculty. Gender differences were generally no-significant, except in fresher recruitment views. The research established a significant relationship between age diversity and teaching performance. This study employed cross-tabulation techniques combining age diversity and gender diversity as independent variables with teaching performance as the dependent variable. This particular approach is unique, as it has not been extensively investigated in prior studies within the Kathmandu Valley context, setting this study apart. Future research could extend this study to encompass educational, experiential, and ethnic diversity's impact on teaching performance.